Quality evaluation of composite flour laddoo containing sprouted and malted ingredients. Issue 4 (11th July 2016) - Agrahar-Murugkar, Dipika; Zaidi, Aiman; Gupta, Chetan
Abstract : Purpose: Development of new products rich in nutrients required for growth and development along with acceptability can contribute in alleviating malnutrition. Laddoo, a traditional sweet, is well-accepted by people at large. However, traditional laddoos contain one or two food groups – sugar and saturated fat, which are not healthy. The aim of this research was to formulate a nutritious laddoo using different food groups and to study its nutritional, functional, textural and sensory profile. Design/methodology/approach: Composite flour laddoo (TL) was formulated using a mix of cereals, sprouted legumes, malted millets, dairy ingredients, fruit, oil and jaggery and evaluated for particle size, colour, texture, nutritional, functional and sensory evaluation and compared with traditional wheat (CL-1) and chickpea (CL-2) flour laddoos (CL). Findings: The TL's were significantly softer in texture compared to CLs, resulting in ease in biting, chewing and swallowing. The nutritional quality of TL was significantly higher in terms of protein (24.6 g/100 g), fibre (3.8 g/100 g), iron (10.4 mg/100 g) and phosphorus (287.5 mg/100 g). The functional quality of TL was also higher in terms of phenolics (123.0 gallic acid equivalent mg/100 g), flavonoids (6.9 quercitin equivalent mg/100 g) and antioxidant activity (62.6 per cent radical-scavenging activity). Organoleptic evaluation also showed higher acceptability (eight) of TL against six for CL-1 and seven for CL-2. Originality/value: Fortification of food products to enhance the nutritive value has become the major focus of the researchers in the field of new product development, owing to the consumer need for products having high nutritive and sensorial properties. Malnutrition is a serious matter of concern among the population of India, and the present situation demands development of products that are rich in nutrients required for growth and development and readily acceptable. Traditional laddoos made using a single ingredient does not provide sufficient nutrients, and sugar and saturated fat used for binding are not healthy options. No work on using composite flour along with sprouting/malting, jaggery and unsaturated fat to prepare laddoos with its nutritional, functional and textural properties has been reported.